Multiphase Flow Dynamics 1: Fundamentals - Kolev, Nikolay Ivanov (Springer, 2016)
In its fifth extended edition the successful monograph package “Multiphase Flow Dynamics” contains theory, methods and practical experience for describing complex transient multi-phase processes in arbitrary geometrical configurations, providing a systematic presentation of the theory and practice of numerical multi-phase fluid dynamics. In the present first volume the local volume and time averaging is used to derive a complete set of conservation equations for three fluids each of